2010
DOI: 10.1590/s0100-204x2010000300002
|View full text |Cite
|
Sign up to set email alerts
|

Consistência do padrão de agrupamento de cultivares de feijão conforme medidas de dissimilaridade e métodos de agrupamento

Abstract: O objetivo deste trabalho foi avaliar a consistência do padrão de agrupamento de cultivares de feijão (Phaseolus vulgaris L.), obtido a partir da combinação de oito medidas de dissimilaridade e oito métodos de agrupamento. Treze cultivares de feijão foram avaliadas em nove experimentos conduzidos entre os anos agrícolas de 2000/2001 e 2004/2005, e agrupadas de acordo com caracteres de produção (produtividade de grãos, número de vagens por planta), de fenologia (número de dias da emergência ao florescimento e d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…The cophenetic correlation estimates obtained in the method of the furthest neighbor were 0,58 and 0,77 respectively to the Mahalanobis and Euclidean distances (Table 3). These results were partially higher than the ones obtained by Cargnelutti Filho et al (2010) in studies using beanstalk, as those authors found values from 0,62 and 0,67 for the Mahalanobis and Euclidiana distances respectively.…”
Section: Resultscontrasting
confidence: 60%
“…The cophenetic correlation estimates obtained in the method of the furthest neighbor were 0,58 and 0,77 respectively to the Mahalanobis and Euclidean distances (Table 3). These results were partially higher than the ones obtained by Cargnelutti Filho et al (2010) in studies using beanstalk, as those authors found values from 0,62 and 0,67 for the Mahalanobis and Euclidiana distances respectively.…”
Section: Resultscontrasting
confidence: 60%
“…Cluster analysis was carried out by the unweighted pair group method with arithmetic mean (UPGMA). The cophenetic correlation coefficient (CCC) was established from the Pearson linear correlation between the elements of the cophenetic matrix and the elements of the dissimilarity matrix (Cargnelutti-Filho et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The consistency of the phytochemistry divergence based on the distances was demonstrated by the Mantel test (Mantel, 1967; Smouse, Long, & Sokal, 1986). A dendrogram (Figure 2) with high reliability is shown by a cophenetic correlation of 0.8236 (Cargnelutti Filho et al., 2010), and high consistent correlation (Rohlf & Fisher, 1968; Sokal & Rohlf, 1962). Phytochemical divergence found among the guarana genotypes can be observed in the dendrogram, after the most similar genotypes, based on nine agro‐industrial characters, were clustered into two groups (I and II) and subgroups (Ia, Ib, and IIa), (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic divergence was based on the average Euclidean distances between pairs of the eight guarana plant genotypes for all characters. The dendrogram was constructed on the basis of the dissimilarity matrix (Supplemental Table S1) by the unweighted pair‐group average (UPGMA) method, considering the consistency of the dendrogram by the Mantel test (Mantel, 1967), cophenetic correlation (Cargnelutti Filho, Ribeiro, & Burin, 2010; Supplemental Figure S1), and cut‐off point (Mojena, 1977).…”
Section: Methodsmentioning
confidence: 99%